The Apparent Motion of STEVE and the Picket Fence Phenomena. Issue 20 (16th October 2020) - Gillies, D. M.; Liang, J.; Donovan, E.; Spanswick, E.
Abstract: In this study, we present the first data obtained from the new Transition Region Explorer (TREx) RGB Imager and analyze the apparent motion of STEVE and the Picket Fence structures in an event on 31 August 2019. The structures associated with STEVE are found to feature a fast westward motion (~5–10 km/s). This is consistent with the notions that STEVE is colocated with a fast subauroral ion drift (SAID) channel and that SAIDs play a key role in the production of STEVE. The apparent motion of the Picket Fence structures is much slower (~400–600 m/s) and can be both westward and eastward. This implies that either the Picket Fence is located at different magnetic flux tubes from that of STEVE, with much slower plasma convection speed, or that the motion of the Picket Fence does not follow the plasma convection. Plain Language Summary: The recently mounted Transition Region Explorer (TREx) RGB Imager is designed to capture "true color" images of the aurora and airglow with high time resolution and is thus ideal for the identification and tracking of STEVE (pink/mauve) and the Picket Fence (green) phenomena. Using the first data from the new TREx RGB imager at Lucky Lake, Canada, we analyze the apparent motion of STEVE and Picket Fence structures in an event on 31 August 2019. The structures associated with STEVE display a fast westward motion (~5–10 km/s), which is part of the reason for its acronym ( velocity enhancement ). The apparent motions of the Picket Fence structures are much slower (~400–600 m/s) and can be both westward and eastward. The above information on the motion speed of STEVE and the Picket Fence is important to the ongoing exploration of their underlying mechanisms. Key Points: We analyze the motion of STEVE and the Picket Fence using the first data obtained from the new Transition Region Explorer True‐Color Imager The structures within STEVE show a rapid westward motion (~5–10 km/s), compatible with the speed of a fast subauroral ion drift (SAID) channel The motion of the Picket Fence is much slower (~400–600 m/s) and can be both westward and eastward, implying a strong flow shear with SAID